Prohibiting Sex Purchasing and Ending Trafficking : The Swedish Prostitution Law - Waltman, Max (Stockholm University, Stockholm, Sweden, 2011)
The Swedish prostitution law from 1999, now followed by Norway and Iceland, criminalized the purchaser and decriminalized the prostituted person. This is analyzed as a cogent state response under international trafficking law, particularly to the obligations set forth in the United Nation’s Trafficking Protocol from 2000. The Protocol states that a person is regarded a trafficking victim when, e.g., someone abuses her “position of vulnerability” in order to exploit her. International jurisprudence and social evidence strongly suggest that prostitution, as practiced in the world, usually satisfies this definition. Further, the Protocol urges states to reduce the demand for prostitution and to protect and assist victims, for instance by adopting laws deterring purchasers of sex, and by supporting those exploited in prostitution. Policy makers, such as the U.S. Department of State, are criticized for taking an inadequate position in face of the growing evidence from the Swedish law's impact.The article shows that Sweden has significantly reduced the occurrence of trafficking in Sweden compared to neighboring countries. It also scrutinizes some misinformation of the law's impact, showing for instance that claims alleging a more dangerous situation for those still in prostitution after 1999 were unfounded. In addition, the article addresses remaining obstacles to the law's effective implementation, arguing that in order to realize the law's full potential to support escape from trafficking, the civil rights of prostituted persons under current law should be strengthened to enable them to claim damages directly from the purchasers for the harm to which they have contributed, and for the violation of the prostituted persons' equality and dignity - a position now recognized by the government to some extent by clarifying amendments made in 2011.